2017
DOI: 10.1111/ncn3.12128
|View full text |Cite
|
Sign up to set email alerts
|

Migraine homocysteine‐related: Old and new mechanisms

Abstract: In this review, we discussed how homocysteinemia can induce migraine. Vascular and neurogenic mechanisms of migraine-onset, such as the classical "triggers", were examined. Favourable effects induced on the syndrome by folate supplementation were also illustrated. However, it was recently shown that hyper-homocysteinemia can favor migraine by the production of homocysteic acid.This acts as an agonist of the N-acetyl-aspartame-D receptor, and is a potent neurotoxic stimulus causing migraine. Its detrimental eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Kara et al have shown that the C677T polymorphism on the MTHFR gene can affect migraine susceptibility, with migraine due to the increase in HCY levels in the blood as reported above [ 156 ]. Cacciapuoti demonstrated that in individuals usually suffering from migraine—especially migraine with aura—an increased serum level of HCY may be present [ 157 ]. Among the reasons could be vasodilation or transient thrombosis in HCY-induced cerebral blood vessels [ 156 , 171 ].…”
Section: Pathological Role Of Homocysteinementioning
confidence: 99%
“…Kara et al have shown that the C677T polymorphism on the MTHFR gene can affect migraine susceptibility, with migraine due to the increase in HCY levels in the blood as reported above [ 156 ]. Cacciapuoti demonstrated that in individuals usually suffering from migraine—especially migraine with aura—an increased serum level of HCY may be present [ 157 ]. Among the reasons could be vasodilation or transient thrombosis in HCY-induced cerebral blood vessels [ 156 , 171 ].…”
Section: Pathological Role Of Homocysteinementioning
confidence: 99%